TRAINING AND MENTORING OF LITERACY AND NUMERACY ACTIVITIES THROUGH THE USE OF ICT-BASED BULLETIN INTEGRATED CHARACTER EDUCATION (BICE) MEDIA IN ELEMENTARY SCHOOL 9 MAMBORO - Ahmar, Dewi Satria; Patmasari, Andi; Ahmar, Ansari Saleh; Azzajjad, Muhammad Fath; Rahmawati, Sitti; Ifriana, Ifriana (LPPM Univ. Ibn Khaldun Bogor, 2023)
SDN 9 Mamboro is one of the schools in Palu City that has launched a literacy and numeracy program. Observations conducted by the service team showed that the literacy and numeracy practices at this school were not optimal. The implementation is still at the habituation stage, directing students to read for 15 minutes at the beginning of the lesson and the implementation is not routine. The book collection and the number of students visiting the library were also lacking, the reading corner was inadequate, the learning methods used were conventional and most teachers did not have the necessary skills to create ICT-based learning media. Based on these observations, the service team and the principal agreed to provide training and assistance in literacy and numeracy activities through the use of bulletin integrated character education (BICE) media. The expected goal of this activity is to improve students' literacy and numeracy skills. The average pretest score of literacy and numeracy skills was 38.29 and increased to 84.92 during the posttest.